2019
DOI: 10.5194/amt-12-4455-2019
|View full text |Cite
|
Sign up to set email alerts
|

Identifying persistent temperature inversion events in a subalpine basin using radon-222

Abstract: Abstract. One year of meteorological and atmospheric radon observations in a topographically complex subalpine basin are used to identify persistent temperature inversion (PTI) events. PTI events play a key role in public health due to the accumulation of urban pollutants that they cause. Two techniques are compared: a new radon-based method (RBM), based on single-height 222Rn measurements from a single centrally located station, and an existing pseudo-vertical temperature gradient method (TGM) based on observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Griffiths et al, 2013;Williams et al, 2013;Pal et al, 2015;Salzano et al, 2016;Vecchi et al, 2018), microclimate spatial variability (Chambers et al, 2016;Podstawczyńska, 2016) and impact assessment of atmospheric stability on local air pollution (Perrino et al, 2001;Chambers et al, 2015a;Chambers et al, 2015b;Crawford et al, 2016;Wang et al, 2016a;Williams et al, 2016). Good correlation, at least for the periods of thermally driven PBL convection, was observed in previous studies comparing effective MLH derived by the box model and MLH obtained by modelling approaches based on turbulence variables (Allegrini et al, 1994;Vecchi et al, 2018;Kikaj et al, 2019) or remote sensing techniques (sodar, lidar) (e.g. Salzano et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Griffiths et al, 2013;Williams et al, 2013;Pal et al, 2015;Salzano et al, 2016;Vecchi et al, 2018), microclimate spatial variability (Chambers et al, 2016;Podstawczyńska, 2016) and impact assessment of atmospheric stability on local air pollution (Perrino et al, 2001;Chambers et al, 2015a;Chambers et al, 2015b;Crawford et al, 2016;Wang et al, 2016a;Williams et al, 2016). Good correlation, at least for the periods of thermally driven PBL convection, was observed in previous studies comparing effective MLH derived by the box model and MLH obtained by modelling approaches based on turbulence variables (Allegrini et al, 1994;Vecchi et al, 2018;Kikaj et al, 2019) or remote sensing techniques (sodar, lidar) (e.g. Salzano et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…Salzano et al, 2016). Kikaj et al (2019) successfully identified persistent inversion events in the Ljubljana basin based on 222 Rn measurements. The emission pattern of gaseous traffic related air pollutants in Bern (Switzerland), estimated by a box-model based on radon tracer, with an included advection term, showed an excellent correlation with traffic density (Williams et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bottom-up emission inventories rely on information on the amount of used fuel combined with fuel-specific emission factors (e.g., Bond et al, 2007;Bond et al, 2013;Klimont et al, 2017). Although current emission inventories agree quite well on the main emission sources and regions, there exist significant uncertainties in the emission factors and activity data, used for emission calculation, with recent observationally constrained estimations much higher than the ones traditionally used (Sun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A recently updated United States black carbon emission inventory (Sun et al, 2019) pointed out a decreasing trend of BC emissions from 1960 to 2000, dominated by the vehicle, industrial and residential sectors. Traffic-related BC emission primarily dominates particulate matter (PM) emission, especially in major cities (e.g., Pakkanen et al, 2000;Klimont et al, 2017). Recently, biomass combustion for residential heating has been promoted under the label of renewable fuel and additionally increased due to economic crises and increase in other fuel prices (Crilley et al, 2015;Denier van der Gon et al, 2015;Hovorka et al, 2015;Athanasopoulou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pasquil-Gifford schemes) or not well suited to the heterogeneous urban environment (Richardson number, Monin-Obukhov similarity theory). Consequently, this study employs a combination of two radon ( 222 Rn)-based techniques [5][6][7][8] for diurnal and synoptic timescale stability classifi cation. Radon's well-established history of application in atmospheric mixing studies [9][10][11][12] is testimony to the robustness and versatility of this tool.…”
Section: Introductionmentioning
confidence: 99%